Trends and perspectives in linear statistical inference : proceedings of the LINSTAT2016 meeting held 22-25 August 2016 in Istanbul, Turkey /: proceedings of the LINSTAT2016 meeting held 22-25 August 2016 in Istanbul, Turkey. (2018) - Unknown
No abstract available